Efficacy and safety of replacement treatment in isolated growth hormone deficiency - Ana Belén Ariza Jiménez; María José Martínez-Aedo Ollero; Juan Pedro López-Siguero (Elsevier, 2019)
Introduction: Growth in patients with isolated growth hormone (GH) deficiency is heterogeneous despite treatment due to the low specificity of diagnostic tests, making it necessary to define efficacy variables. Aims: To evaluate efficacy of hormone replacement therapy in children with isolated GH deficiency. Methods: Observational-ambispective study of patients treated in our department in the last 14 years for isolated GH deficiency. This was defined as a GH level less than 7.4 mg/dL in response to 2 stimulation tests in patients with height < 2SD and a decreased growth rate. Results: The study included a total of 97 patients, of whom 69% were boys. The large majority (89.58%) achieved final height. None of them had side effects. The median dose of GH used was 0.028 mg/kg/day (0.03-0.025). There was a gain of 1.17 SD in final height. Around three-quarters (71.13%) of the patients were reassessed in adulthood, of whom 39.4% maintained the deficiency, and 79.31% achieved target range height. Target height, estimated height, and the total pubertal gain were positively correlated with final height, while the bone age/chronological age ratio and the initial insulin-like growth factor-1 showed a negative correlation. Conclusions: A majority of patients reached target size, although only a few of them maintained the deficiency in adulthood. Target size, estimated adult height, and pubertal variables are directly related to adult height, while bone age/chronological age and insulin-like growth factor-1 were inversely related, and these can be used as efficacy variables. No adverse effects were observed in the sample with the doses used for the treatment. Resumen: Introducción: El crecimiento en pacientes con déficit aislado de hormona del crecimiento (GH) es heterogéneo a pesar del tratamiento, debido a la baja especificidad de las pruebas diagnósticas, por lo que es necesario definir las variables de eficacia. Objetivos: Evaluar la eficacia de la terapia de reemplazo hormonal en niños con déficit aislado de GH. Métodos: Estudio observacional-ambispectivo de pacientes tratados en nuestro servicio en los últimos 14 años por déficit aislado de GH, definido como GH inferior a 7,4 mg/dl en 2 pruebas de estímulo, en pacientes con talla < −2DE y velocidad de crecimiento disminuida. Resultados: Se estudiaron 97 pacientes. El 69% eran varones. Con el tratamiento hubo una ganancia de talla de 1,17DE. El 79,31% alcanzaron la talla diana. El 71,13% fueron reevaluados en la edad adulta, de los cuales el 39,4% mantuvo el déficit. La talla diana, el pronóstico de talla adulta y la ganancia puberal total se correlacionaron positivamente con la talla adulta, mientras que la relación edad ósea/edad cronológica y factor de crecimiento insulínico tipo 1 inicial mostraron una correlación negativa. Ninguno tuvo efectos secundarios. Conclusiones: La mayoría de los pacientes alcanzaron la talla diana, aunque no todos mostraron permanencia del déficit en edad adulta. La talla diana, el pronóstico de talla adulta y las variables de pubertad están directamente relacionados con la talla adulta; mientras que la edad ósea/edad cronológica y factor de crecimiento insulínico tipo 1 están inversamente relacionadas, pudiendo utilizarse estas como variables de eficacia. No se han observado efectos adversos en la muestra con las dosis utilizadas.